Application of global positioning system (GPS) in forestry / Nazliah Husin - Husin, Nazliah (2002)
Future generations can enjoy the benefits of the Malaysia's forest resource, better, and more careful sustainable development of our forest resources is needed. In the establishment of sustainable development of this forest resources, planners, managers, policy maker and researchers alike need to understand the complexity of factors involved. They must collect and interpret the required data and work together with professional from other disciplinary fields (Kamaruzaman, 2002). Forest management practices can be improved through the use of current technologies including Remote Sensing, Geographic Information System (GIS), and Global Positioning System (GPS) (Khali et. al, 2002). GIS is satellite technology that is used to make observations and photographic images of the earth's surface feature and conditions. GPS is the use of satellite technology to accurately and consistently identify exact locations (Burton, 1999). Figure 1 showed a Global Positioning System (GPS) (Mohd Hizamri, 2002).